Análisis de los métodos en el nuevo libro de inglés en los estudiantes de noveno año de educación básica de la Unidad Educativa Isabel de Godín ciudad de Riobamba provincia de Chimborazo durante el año lectivo Septiembre 2016 Febrero 2017. - Barreno Freire, Eduardo Santiago (2017)
Nowadays, traditional and innovative teaching methods are critically examined, evaluated and some modifications in the teaching are suggested. Traditional methods are still used. For this reason, the present scientific research aims to analyze the methods proposed in the new book of English used by students of the 9th year of Basic General Education of Unidad Educativa Isabel de Godín, Riobamba City, Chimborazo province. In order to predict whether the methods contained in the books delivered by the state are appropriate for the students of this institution. In addition, we want to identify if the CLIL, CLT and CL methods are known and how to adapt them in contexts such as the one presented in this study. The approach is qualitative with the characteristics of exploratory and descriptive in which the ethnographic method was used to describe the things that were happening in this environment. The population was made up of 54 students and a teacher of the 9th year. In addition, the techniques and instruments used to gather the data were observation guides. The main findings demonstrate that methods such as CLIL, CLT and CLM promote the development of communicative capabilities that foster student integration and participation. It was observed that the use of the methods was not adequate.